This is really war the incredible true story of a Navy nurse POW in the occupied Philippines - Lucchesi, Emilie Le Beau (Chicago Review Press, 2019)
"The story of US Navy nurse Dorothy Still and her colleagues at a military hospital in the Philippines, who cared for their fellow prisoners of war while being held captive by the Japanese during World War II"--